2017
DOI: 10.1126/scisignal.aag3326
|View full text |Cite
|
Sign up to set email alerts
|

PSMA redirects cell survival signaling from the MAPK to the PI3K-AKT pathways to promote the progression of prostate cancer

Abstract: Increased abundance of the prostate-specific membrane antigen (PSMA) on prostate epithelium is a hallmark of advanced metastatic prostate cancer (PCa) and correlates negatively with prognosis. However, direct evidence that PSMA functionally contributes to PCa progression remains elusive. We generated mice bearing PSMA-positive or PSMA-negative PCa by crossing PSMA-deficient mice with transgenic PCa (TRAMP) models, enabling direct assessment of PCa incidence and progression in the presence or absence of PSMA. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 84 publications
2
49
0
Order By: Relevance
“…In our recent work published in Science Signaling, 9 we demonstrate that expression of PSMA in prostatic epithelial cells directly underlies prostate tumor progression in vivo by crossing FOLH1 global knockout mice 10 (hereafter called PSMA knockout) with the well-characterized TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) murine model to study PC tumor progression in the absence of PSMA expression. We observed that the primary tumors in wild-type animals were larger than tumors in the PSMA knockout animals and were highly vascularized, with higher rates of progression from hyperplasia to adenocarcinoma.…”
mentioning
confidence: 99%
“…In our recent work published in Science Signaling, 9 we demonstrate that expression of PSMA in prostatic epithelial cells directly underlies prostate tumor progression in vivo by crossing FOLH1 global knockout mice 10 (hereafter called PSMA knockout) with the well-characterized TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) murine model to study PC tumor progression in the absence of PSMA expression. We observed that the primary tumors in wild-type animals were larger than tumors in the PSMA knockout animals and were highly vascularized, with higher rates of progression from hyperplasia to adenocarcinoma.…”
mentioning
confidence: 99%
“…This finding was further supported by a mouse model study which indicated that moderate PSMA expression facilitates prostate carcinogenesis in vivo . Increased PSMA expression has been shown to induce aneuploidy and activate AKT signaling, and the over‐expression of PSMA may promote prostate carcinogenesis through several different mechanisms. Our data suggest that inactivation of Sox7 may provide multiple advantages for prostate carcinogenesis because it leads to the aberrant activation of WNT signaling and the over‐expression of PSMA.…”
Section: Discussionmentioning
confidence: 74%
“…While PSMA is moderately expressed in benign and hyperplastic prostate tissues, its expression level has been shown to be associated with increased tumor stage . An increased level of PSMA expression may directly contribute to prostate cancer development because PSMA induces aneuploidy and activates AKT signaling . Furthermore, a mouse model study indicated that moderate PSMA expression facilitates prostate carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Out of three PSMA/GCPII‐deficient colonies established to date, only one (IMPC) had the PGK‐Neo cassette removed using the Cre‐Lox system before the mice were characterized . The other two PSMA/GCPII‐deficient colonies, which are routinely used for diverse experiments, likely do not contain any LoxP sites, and PGK‐Neo cassette removal is thus not possible.…”
Section: Discussionmentioning
confidence: 99%